Annual Plan 1986-87 Orissa (Draft) - Planning Commission (Planning Commission, 1985)
The Annual Plan 1986-87, which provides the blue -print for plan programmes in the second year of the Seventh-Plan carries forward the objectives and priorities underlying the threshold Year Plan of the preceding year, 1985-86. the Seventh Plan of the State follows the basic priorities of the National Plan, namely, maximisation of food production, enhancement in employment generation and faster rate of production in all sectors of development. Within these parameters the Annual Plans have been framed conformity with the needs of the State and the resources available for the purpose. The operational strategy of the Annual Plan 1985-86 was to consolidate the gains of the Sixth Plan and maintain the growth already achieved. Emphasis was, therefore, placed on speedy completion of the incomplete works and making new starts selectively with an eye to their long-term benefit- It is thus that in crucial sectors like agriculture, irrigation, communication, power, water supply, industries, etc.
Government of Orissa